Solid Wastes Toward Flame Retardants for Polymeric Materials: A Review - Gao, Chuanhua; Huo, Siqi; Cao, Zhenhu (Frontiers in Materials, 2021)
It has been significant yet challenging to recycle and reuse different kinds of wastes due to their mass production with the society development. Many efforts have been conducted to reuse wastes in different fields. Interestingly, some wastes have been employed to replace traditional petroleum-based flame retardants for polymeric materials. This review focuses on the recent development of waste flame retardants and their impacts on thermal stability, flame retardancy and smoke suppression of polymers, followed by representative flame-retardant mechanisms. Finally, the key challenges associated with waste flame retardants are presented, and some perspectives in the future are proposed.